Of pacemakers and statistics: the actuarial method extended. - Dussel J; Wolbarst AB; Scott-Millar RN; Obel IW (Pacing & Clinical Electrophysiology, 1980)
Pacemakers cease functioning because of either natural battery exhaustion (nbe) or component failure (cf). A study of four series of pacemakers shows that a simple ex- tension of the actuarial method, so as to incorporate Normal statistics, makes possible a quantitative differentiation between the two modes of failure. This involves the separation of the overall failure probability density function PDF(t) into constituent parts pdfnbe(t) and pdfcf(t). The approach should allow a meaningful comparison of the characteristics of different pacemaker types.